PENENTUAN HARGA POKOK PERHIASAN EMAS ANTARA HITUNGAN ECER DAN KULAK DALAM KONTEKS TOKO PERHIASAN EMAS DI JAWA TIMUR - Rina Puspita; Agus Subandoro; Sari, Anita Kartika (Ekomania, 2023)
The purpose of this study was to determine how to determine the true price of gold jewelry from a retailer and a consumer point of view.  So that we can find out the value of profits in investing in gold jewelry from the perspective of entrepreneurs, retailers and also from a consumer perspective.  The determination of the price of gold jewelry generally refers to the US $ dollar value and also the exchange rate from the entrepreneur to the factory.  The results of this study indicate that gold jewelry has a high investment value and also affects the daily economy of those who own it because it can be operated if at any time they need emergency funds and the price can soar every year.